Evaluation of the Anti-inflammatory Activity of Atorvastatin and its Effect on Alveolar Diameter in a Model of Elastase-induced Emphysema in Rats - Boiati, R. F.; Manchini, M. T.; Jacobsen, O.; dos Santos Batista, J. G.; Silva Júnior, J. A.; Nascimento, J. W. L. (Drug Research, 2015)
Statins are cholesterol-lowering agents and some of them, like simvastatin, have anti-inflammatory effects. In this study, we evaluated the effect of atorvastatin on nitric oxide (NO) release, leukocytes levels and alveolar diameter related to the inflammatory process associated with elastase-induced emphysema in rats. 32 rats were divided into 4 groups, n=8: control (C), atorvastatin (A), emphysema (E), and emphysema+atorvastatin (EA). On day 0 (zero), groups C and A received intratracheal instillation of saline (0.2 ml), and groups E and EA received elastase (0.2 ml). Groups A and EA received atorvastatin (20 mg/kg) and C and E received vehicle, by gavage, for 25 days. Animals were euthanized, slices of lung stained and the alveolar diameters measured. Data obtained show that the treatment with atorvastatin (EA group) did not reduce the alveolar diameter (35.3 vs. 32.3), NO (2.7 vs. 3.0 μM) or the leukocyte count (111 vs. 136) compared with the E group, indicating that different statins, like simvastatin or atorvastatin, have different behavior in inflammatory processes like in elastase-induced development of emphysema in rats.
Keywords: statin; COPD; emphysema; inflammation; leukocytes; lung